2000
DOI: 10.1038/35039551
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of fibroblast growth factor receptor ectodomain bound to ligand and heparin

Abstract: Fibroblast growth factors (FGFs) are a large family of structurally related proteins with a wide range of physiological and pathological activities. Signal transduction requires association of FGF with its receptor tyrosine kinase (FGFR) and heparan sulphate proteoglycan in a specific complex on the cell surface. Direct involvement of the heparan sulphate glycosaminoglycan polysaccharide in the molecular association between FGF and its receptor is essential for biological activity. Although crystal structures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
580
5
4

Year Published

2001
2001
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 652 publications
(621 citation statements)
references
References 29 publications
28
580
5
4
Order By: Relevance
“…Approaching heparin molecules in solution can therefore bind with only small torsional changes on its stable conformation, which is consistent with previous observations of experimental heparin structures (PDB code 1hpn) or co-crystallysed complexes (eg. PDB codes 1rid, 1bfc and 1e0o) (Faham et al, 1996;Ganesh et al, 2004;Mulloy et al, 1993;Pellegrini et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Approaching heparin molecules in solution can therefore bind with only small torsional changes on its stable conformation, which is consistent with previous observations of experimental heparin structures (PDB code 1hpn) or co-crystallysed complexes (eg. PDB codes 1rid, 1bfc and 1e0o) (Faham et al, 1996;Ganesh et al, 2004;Mulloy et al, 1993;Pellegrini et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Data from microscopy, covalent cross-linking, and x-ray crystallography experiments have revealed that cell surface receptors from many structural classes assemble into multi-receptor complexes; these include some heptahelical G-protein coupled receptors (GPCRs), [36][37][38] methyl-accepting chemotaxis proteins (MCPs), [39] gated ion channels, [40] receptor protein tyrosine kinases (RPTKs), [41,42] and multichain immune recognition receptors (MIRRs). [22,33,35,[43][44][45] The size of these ensembles varies: Some complexes are composed of two receptors while others contain thousands.…”
Section: Signaling Complexesmentioning
confidence: 99%
“…At the cell surface, HSPGs contribute to the formation of a ternary complex with two FGF molecules and one growth factor receptor chain, which form an "activated" unit (34). The HSPGs can also serve as important reservoirs for other angiogenic factors.…”
Section: Hspgs As Depots For Pro-and Antiangiogenic Factorsmentioning
confidence: 99%